Analyzing The Influence of Motivation and Discipline On The Employees Performance of PT. Xyz - Ahmad Yani; Suharno Pawirosumarto (Dinasti International Journal of Education Management And Social Science, 2024)
The study was conducted to analyze the influence of Motivation and Discipline on PT. XYZ’s Employees Performance. The analysis methods used in this study are quantitative research and multiple linear analysis on SPSS. Within this research, the researcher used the Slovin formula to determine total numbers of respondents, from a total of 451 employees of PT. XYZ, 82 of total employees are eligible to participate as respondents. The result of this research showed that there is a positive influence and significant effect between Motivation and Discipline on Employees Performance whether simultaneously and or partially. Furthermore, the Discipline variable has the strongest influence on Employee Performance rather than Motivation variable. Therefore, the researcher strongly suggests PT. XYZ management to be more attentive to their employees’ Motivation in order to enhance Employees Performance.